Harmony of Eschatological Meanings: Between Christian Concept and Manggarai Culture in Indonesia - Denar, Benediktus; Tolo, Paulus; Julivadistanto, Thomas (Asosiasi Ahli Filsafat Keilahian Indonesia, 2023)
The Catholic Church is over 100 years old in Manggarai, Flores, Indonesia. The teachings of the Catholic Church are readily accepted by local people, partly because the beliefs of the local people of Manggarai are compatible with the instructions brought by the Catholic Church. This is especially evident, for instance, in the understanding, belief and appreciation of the local community regarding eschatology. Employing an ethnographic-theological study, this article reflects a contextual approach to theology. The method used is an ethnographic-theological study. The data was obtained by direct observation, interviewing traditional Manggarai leaders who are Catholics, and studying some documents related to this article's subject. This study addresses the following question: how does the vision of the Manggaraian people's future help the inculturation of Catholic eschatology? According to the research question, this article explores the basis of hope for the end of the Manggaraian people and simultaneously compares it with the existing Christian eschatology. This study shows a harmony between the eschatological meaning of the Manggaraian local beliefs and that of the Catholic Church. This harmony facilitates the inculturation of Catholic eschatological beliefs into the local culture of the Manggaraian community. This page is in English Translate to Indonesian AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate English to IndonesianPRO Never translate English Never translate aafki-afti.org